Gravity wave modulation of gradient drift instabilities in mid-latitude sporadic E irregularities - Woodman Pollitt, Ronald Francisco (1991)
Recent E region VHF backscatter echoes observed by the MU radar at mid-latitudes show quasiperiodic striations with a fairly constant range vs. time tilt in a RTI display. These features are explained in terms of gravity waves with frequencies close to the Brunt-Väisälä frequency which modulate the shape of sporadic E layers. The conditions of instability, when the magnetic field has a significant dip angle, is revised. Differing from previous work, we argue that conditions of local gradient drift instability are not sufficient and one has to consider the integrated properties of each magnetic filed tube. Stratified sporadic E layers are stable using this new criteria, unless they are distorted to produce unstable integrated gradients. Gravity waves with phase fronts parallel to the magnetic dip angle are capable of producing such distortion, imposing its own temporal and spatial periodicity on the echoes.